2014
DOI: 10.1111/cyt.12133
|View full text |Cite
|
Sign up to set email alerts
|

Impression cytology diagnosis of ulcerative eyelid malignancy

Abstract: Impression cytology is a simple, useful, non-invasive technique for the detection of malignant ulcerative eyelid lesions. It is especially useful as a follow-up technique for the detection of recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…ICS and CBS provided samples with equal cell quality in healthy and diseased horses. In human ophthalmology, ICS is used for the diagnosis of ocular surface tumours as cells harvested with ICS are of highest quality [4,9,10,25]. In the current study, the 2 cases of SCC were identified with both ICS and CBS.…”
Section: Discussionmentioning
confidence: 90%
“…ICS and CBS provided samples with equal cell quality in healthy and diseased horses. In human ophthalmology, ICS is used for the diagnosis of ocular surface tumours as cells harvested with ICS are of highest quality [4,9,10,25]. In the current study, the 2 cases of SCC were identified with both ICS and CBS.…”
Section: Discussionmentioning
confidence: 90%
“…This limitation was already reported in human medicine when the diagnostic accuracy in detecting ocular neoplasia was compared between IC and histopathology. There was a high positive predictive accuracy, but only a fair negative predictive value of IC in identifying ocular surface neoplasia in one study, and another described a good sensitivity in detecting the presence of a neoplastic cells, but a low sensitivity in identifying the type of malignancy in eyelids . In all these studies, the main limitation identified for the IC was the loss of clarity of cytologic details.…”
Section: Discussionmentioning
confidence: 97%
“…Because of its low sensitivity in terms of cytological categorization of the type of malignancy, IC cannot be recommended in the primary diagnosis of eyelid malignancies. Nevertheless, with experience and improvement in the technique, it may prove to be a useful tool in deciding future management, particularly in recurrences of histopathologically confirmed eyelid malignancies, where biopsies may be avoided (36) .…”
Section: Application Of Ic In the Evaluation Of Ulcerative Eyelid Malmentioning
confidence: 99%